SURGICALLY INDUCED ASTIGMATISM AFTER PHACOEMULSIFICATION WITH CLEAR CORNEAL 3.2 MM INCISION WHILE USING SUPERIOR VERSUS TEMPORAL APPROACH - Muhammad Saad Ullah; Syed Ahmer Hussain; Rabia Farhat (Journal of University Medical & Dental College, 2015)
ABSTRACT OBJECTIVE: The aim and objective of this study was to assess surgically induced astigmatism followed by phacoemulsiﬁcation with clear corneal 3.2mm incision while using superior versus temporal approach. MATERIAL AND METHODS: This study was carried out at the department of Ophthalmology Ghazi Medical College and Teaching Hospital Dera Ghazi Khan. The sample size was 200 eyes of 180 patients. In all the patients, clear corneal incision was used. The patients were divided into two groups. Group-I included 100 eyes of 94 patients who underwent surgery via temporal approach. Group- II included 100 eyes of 86 patients in whom superior approach was used. Keratometry was performed preoperatively, on ﬁrst post operative day, after 2 weeks and 8 weeks. Surgically induced astigmatism was calculated by comparing preoperative and post operative keratometric readings at 8 weeks. RESULTS: 200 eyes of 180 patients were the sample size of this study. 79 were male with Mean 59.76+0.5) and 101 were females with Mean 60.61+0.2. Mean age ranged 45-70 years was 60.24+0.3. The surgically induced astigmatism in group I ranged from 0.25D to 0.85D with Mean 0.48D and in Group II ranged from 0.75D to 1.50 D with Mean 0.99D. CONCLUSION: For a suture less clear corneal incision temporal approach results in considerably less degree of surgically induced astigmatism.